Caderneta de saúde da pessoa idosa no olhar de idosos atendidos na estratégia saúde da família - Dantas, Kiara Maria Vieira Pinto (2015)
Introduction: The ageing population is a global reality, even in developing countries people have never had a chance to live so long. This new demographic situation caused the necessity to develop legal provisions to guide social and health actions. Among them, the National Health Policy for the Elderly, marked by the paradigm of the functional capacity and along with it comes the Health Handbook of the Elderly, which represents a delimitation instrument of the profile of the elderly, identifying frail elderly people or in the process of embrittlement, collaborating with the formulation of health actions focused on aging well. Objective: The objective of this study is to know the social representations of elderly about the health booklet of the elderly and to understand its membership in the context of primary care. Methodology: This is an exploratory-descriptive study with a qualitative approach performed with 103 elderly people with age above sixty years at the units of the Sanitary District V. The study was conducted between July and September 2014, respecting the ethical criteria of the Resolution 466/12.The data collection was performed by a semi-structured interview contemplating questions related to the booklet. The socio-demographic data were analyzed twice once using Categorical Thematic Content Analysis Technique, which showed six classes or categories: 1) Support for the service; 2) Guidance tool for the elderly; 3) Modality of health information; 4) Descriptions of complications in health; 5) Types of monitoring the health of the elderly; 6) security instrument; referring to two dimensions of social representations: information and knowledge about the book and the position or attitude of the elderly. The second analysis was carried out using Iramuteq 0.7 software was responsible for the social representations: images and representation field of the booklet. Results: Among the interviewed elderly, 40.8% said that they use the booklet, 48.5% affirm that they do not have knowledge about the book and 10.7% have the book but do not use it. In addition, 83.5% of the elderly are female and 78.6% with age between 60-70 years. The results show representations of positive content related the use of the book showing a good acceptance of this, besides recognizing it as a facilitator instrument for the care of the elderly defined in six categories. The elderly utilize the booklet as security and protection. The elderly people who do not use the book justify not using it due to lack of information. Conclusion Having the opportunity of knowing the elderly social representations about the health booklet for elderly was important to get to know and understand the thinking of the elderly in relation to the booklet and the significance of these representations. It is expected that this study will stimulate further research in the social representations in the ambit concerning the health booklet for elderly, in compliance with the National Health Policy for the Elderly.